Uma abordagem sobre as doenças ocupacionais - Sicoli, Elyseu (2011)
The Cumulative Trauma Disorders (CTD) hás been common in various professions that require repeating the same movement several times thoughout the day. The professionals more affected by this problem, are: workers in production lines, cash drawers operators, homemakers, dentists, and others. Also called by work Related Musculoskeletal Disorders (WRMD) or Musculoskeletal Disorders Related to Working (MDRW), these lesions are caused by the repetitive or forced use of the muscles groups or inadequate posture. The most common symptoms are ache, tingling feelings, mysterious numbness, muscle fatigue and peripheral nerves. Several factors have been making that the personal and Professional life is much affected: intense and chronic sumptoms, lack of prevention and rehabilitation policies by the companies, late diagnosis and treatment, among other. Objective: The purpose of this work was to asses the knowledge degree of the professionals ins São José do Rio Preto among the occupational diseases and improve education in the graduation about these occupational illnesses so that students in future can prevent the same problem. Methods: The learners participating in this project went to the dental clinics of São José do Rio Preto, and explained the objectives as well as the Term of Free and Informed Consent. They made the interview with the professional using a questionnaire, avoiding the interference or reading of the data by others. The listing of clinics was obtained through the Regional Council of Dentistry Station of São José do Rio Preto. The questionnaire addressed questions since the knowledge of the diseases through what the professionals do to avoid them. The questionnaire also had the objective of selecting samples. Interesting results were obtained through research, such that 42.85% of participants already had some joint pain manifestation, which may be signs of repetitive strain injury and that nearly 99% of workers had some basic ergonomics in your graduation, but only 63.63% implemented in your office. The project was submitted by the Ethical Committee, and the volunteers that agreed in participating on the study signed a free and informed consent, as resolution 196/96 of the National Council of Ethics and the search of the Health Ministry.